Gel cream loaded with Lafoensia pacari phenolics-containing extract with antioxidant and photoprotective activities - Caixeta, Eliane Vasconcelos (2024)
Universidade Federal De Goiás. Faculdade de Farmácia. Laboratório de pesquisa de produtos naturais. Goiânia, GO, Brasil.